Community activity pavilion and community recreation center [copy transparency] - Palm Springs Collaborative::::::::: (1970)
Rendering of activity pavilion and recreation center exterior. Drawing is attributed to the Palm Springs Collaborative, whose members include John J. Cody, Donald A. Wexler, and Patrick Sheehy. The drawing lists William F. Cody as the City Architect.